Biometry, condition factors and length-weight relationships of sixteen fish species in Iwopin fresh-water ecotype of Lekki Lagoon, Ogun State, Southwest Nigeria - O.O. Famoofo; W.O. Abdul (Heliyon, 2020)
Study on biometry, length-weight relationships and condition factors of 139 fishes covering 11 families and 16 species inhabiting Iwopin fresh water ecotype of Lekki Lagoon, were provided. The fish species were obtained from the major landing sites of Iwopin from July to September, 2017. As a result, Chrysichthys nigrodigitatus was the most abundant while Polypterus senegalus, Sphyraena barracuda and Dagetichthys lakdoensis constituted the least groups of populations. The Fulton condition factor (K) values significantly (P < 0.001) ranged between 0.80 and 1.28 while b values varied from 1.067 to 3.41. The values of b indicated negative and positive allometric growth patterns. The highest mean total length value (33.2 ± 1.55) cm was found in Papyrocranus afer while the least mean total length value (7.9 ± 0.60) cm was found in Sarotherodon galilaeus. S. barracuda had the highest mean weight value (187.0 ± 72.9) g while S. galilaeus had the least mean weight value.